Cancer metabolism rewiring and chromatin methylation: a vulnerable epi-metabolic link - Atlante, Sandra; Barbi, Veronica; Gaetano, Carlo; Illi, Barbara (Frontiers in Epigenetics and Epigenomics, 2025)
Over the past few years, significant advances have been made in understanding the crosstalk between cancer metabolism and gene expression. Whereas higher levels of expression of metabolic enzymes may be considered a conceivable compensatory mechanism to satisfy the increasing request of energy of tumor cells, the detection of changes in the amount and species of intermediate metabolites (oncometabolites) and the discovery of their functional role as co-factors and structural components of chromatin modifiers tightened the link between metabolic shifts and epigenome reshaping in cancer. Changes in the chromatin methylation landscape are one of the epigenetic fingerprints of cancer metabolic rewiring associated with the tumorigenic features of neoplasms. Thus, we propose targeting metabolic enzymes directly involved in cancer methylome remodeling and oncometabolite-dependent chromatin modifiers as innovative tools to reset the epigenome of deregulated cancer cells.